2015
DOI: 10.1161/hypertensionaha.114.04775
|View full text |Cite
|
Sign up to set email alerts
|

Interplay Between Connexin40 and Nitric Oxide Signaling During Hypertension

Abstract: A fter a chronic increase in blood pressure, arteries undergo alterations of endothelial (ECs) and smooth muscle cells (SMCs) because of hemodynamic changes.1 Specifically, hypertension results in the hypertrophic remodeling of arterial walls, 2,3 which associates with altered expression of connexins (Cxs). [4][5][6][7][8] These proteins form channels for the communication of ECs and SMCs, which is needed to coordinate vasoconstriction and vasodilation along the vessels.9 ECs predominantly express Cx37 and Cx4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 38 publications
3
13
0
Order By: Relevance
“…G). This data is in agreement with previous reports showing a role of CX40 in ECs in association with the EC marker eNOS . Therefore, these experiments demonstrate that ESM1 regulates the expression of EC markers such as eNOS and CD144 through an association with CX40, an important EC gap junction channel component, possibly due to increased formation and stability of gap junctions, which are essential functional EC characteristics.…”
Section: Resultssupporting
confidence: 93%
“…G). This data is in agreement with previous reports showing a role of CX40 in ECs in association with the EC marker eNOS . Therefore, these experiments demonstrate that ESM1 regulates the expression of EC markers such as eNOS and CD144 through an association with CX40, an important EC gap junction channel component, possibly due to increased formation and stability of gap junctions, which are essential functional EC characteristics.…”
Section: Resultssupporting
confidence: 93%
“…Restoration of Cx40 expression in endothelial cells from Cx40-deficient mice normalizes eNOS levels [93], suggesting a link between these proteins. Volume-dependent hypertension (one kidney, one clip model) promotes the interaction of both Cx40 and Cx37 with eNOS resulting in increased release of NO [93]. Contrary to what was previously shown for Cx37's effect on eNOS function in vitro, vascular reactivity studies demonstrated that basal NO release and the sensitivity to acetylcholine are decreased in aortae from Cx37 −/− and Cx40 −/− mice but not in Cx40 +/− mice [94].…”
Section: Interactions Indirectly Affecting Enos Functionmentioning
confidence: 95%
“…This effect has been linked to reduced eNOS expression in Cx40-deficient mice [92]. Restoration of Cx40 expression in endothelial cells from Cx40-deficient mice normalizes eNOS levels [93], suggesting a link between these proteins. Volume-dependent hypertension (one kidney, one clip model) promotes the interaction of both Cx40 and Cx37 with eNOS resulting in increased release of NO [93].…”
Section: Interactions Indirectly Affecting Enos Functionmentioning
confidence: 96%
“…How endothelial Cx40 controls blood pressure remains poorly understood but might be attributable to endothelial nitric oxide synthase activity, an important modulator of vascular tone. 40 Interestingly, both ALK1 and Cx40 interact and regulate the activity of endothelial nitric oxide synthase, 33,41 suggesting that the phenotype of the Acvrl1 +/− ; Gja5 EGFP/+ mice may be at least partially attributable to uncoupled endothelial nitric oxide synthase activity. To support this hypothesis, we have found an increase production of reactive oxygen species in the lung arteries of Acvrl1 +/− ; Gja5 EGFP/+ mice.…”
Section: Discussionmentioning
confidence: 99%